MENDESAIN HUBUNGAN KABINET DENGAN GUBERNUR DALAM SISTEM PRESIDENSIAL INDONESIA - Rizki Jayuska (JURNAL LITIGASI (e-Journal), 2020)
Article 4 paragraph 1 of the 1945 Constitution concerning the President of the Republic of Indonesia holds governmental authority under the Constitution. However, Governor elected sometimes set up policies ultra vires for they thought that they held legitimacy to exercise the power from their consituents. Poor coordination between Cabinet and the Governor and program mismatched implicated in bad development program and public service in the region. President, in the context of presidentialism, is the apex of hierarchy. The Cabinet must be loyal to the president not to other patrons. Proposal to grant a ministerial power level of position and role to the Governor or to provide seats for Governor and Deputy Governor at the cabinet meeting is worth a consideration. In addition to lessen the miscommunication with the Cabinet, it is also to ease the works of the Cabinet in the regions. Governor and the Cabinet would have a good relationship whenever the program and policy of the Cabinet are transparently conveyed to all governors and when people are also informed. Participation should be developed on the ground of freedom of speech. Therefore, the decision-making process in the Cabinet that was formerly hierarchical will shift to the process involving the entire people of Indonesia. Certainly, the mechanism of this participation would be easier if the representative of the governor or the Governer seats in the Cabinet and vice versa. Keywords: Cabinet, governor, president, presidential system.